Rotary-throwing strength training and testing - Hong, T.; Chen, B.; Cui, G. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Rotary-throwing strength training has always been a very difficult training problem in the World. This paper researched several creative training methods and equipment in order to measure and evaluate an individuals rotary-throwing strength more accurately, improve the maximum capacity of rotarythrowing, and make a breakthrough in rotary-throwing performance. Methods Theoretical, mechanical and electronic design methods were used as well as a human movement test. Results A rotary-throwing strength training and testing apparatus was designed and created. The maximal rotary working load of the shoulder and arm was 1960N and 1570N for the hip. The maximum rotary working distance of the shoulder and arm was 300° and 260° for the hip. Discussion There are two necessary conditions for the rotary-throwing strength training. Firstly, the trunk must be resisted and fully twisted. Secondly, the lower body (below hip) must be fixed. In order to achieve the first condition, a resistance device which revolves around the shoulder axis must be designed to ensure that the trunk fully twists and the resistance load of the arm is appropriate. A method for achieving the second necessary condition is to design a hip and leg fixing device. This system makes the hip travel ahead of the shoulder with an angular difference. The device can ensure the full twist between the shoulder and hip. To achieve hip resistant rotation training identical to the real throwing technique, a hip resistant rotational device must be designed, which rotates around the longitudinal axis of the body and attaches to the hip. When doing rotation exercises with the hip rotation resistant device, the foot and leg must positively travel ahead of the hip, so as to create a greater angular difference between the hip and shoulder. Conclusions Rotary-throwing strength training and testing apparatus can assist the improvement of performance and testing of maximal rotation strength of the shoulder and hip. With excellent training security the training method makes training load and training efficiency several times greater than the traditional method. The application of these methods is important in developing potential in rotary-throwing and improvement of results. Rotary strength testing devices can test many mechanical indices of multi-joint rotating exercises, including rotation strength, rotation speed, and rotation power of the hip and trunk. The function provides a new method which may provide valuable parameters for skill analysis, assessment of specific sport capacity and the study of skills related to throwing events.